Sistem Numeralia dalam Bahasa Namblong - Yulius Pagappong (Balai Bahasa Provinsi Papua, 2019)
Numeral is a word for counting the number of people, animals, things, and consepts. Basically, there are two kinds of numeral as Indonesian, they are cardinal and ordinal. Cardinal refers to the answer of question